Chemical data of Roman pottery in Germania Inferior and beyond - Schneider, Gerwulf (Rei Cretariae Romanae Fautorum Acta, 2017)
This paper aims at presenting an overview on archaeometric analyses of Roman pottery from sites in Germania Inferior and neighbouring Roman provinces carried out since 1975 at the Free University of Berlin (FUB). All pottery samples have been analysed using wavelength-dispersive X-ray fluorescence (WD-XRF). Many samples have also been studied in thin-section and by MGR-analysis. All data from these chemical analyses are recorded in the same format and collected in a database which is currently being prepared as a web-portal. There are two reasons to do this now. Firstly, many of the data available in Berlin have not been published with the detailed data of all sherds analysed, or they are less easy to find than it is now made possible using the internet. Secondly, the rapidly growing use of portable X-ray fluorescence (pXRF) as a tool for limited but fast chemical analysis of ceramics needs accurate data for comparison when the chemical compositions will be used to determine provenances of pottery samples.